The physiological responses to volume-matched high-intensity functional training protocols with varied time domains - Smith, Jessica S.; Bellissimo, Gabriella F.; Amorim, Fabiano T. (Frontiers in Physiology, 2025)
BackgroundHigh-intensity functional training (HIFT) is typically performed with minimal or no rest periods, including “rounds for time” (RFT) or “as many rounds or repetitions as possible” (AMRAP) design. Alternatively, some HIFT workouts can be performed with prescribed rest intervals (e.g., “every minute on the minute” [EMOM]) that may have significant effects on physiological responses.PurposeTo compare the physiological responses between two different HIFT workouts (EMOM and RFT) that were matched for total work volume (TWV).MethodsTwelve trained individuals (six males and six females) performed two HIFT protocols, EMOM and RFT. Both the EMOM and RFT included five rounds of five power cleans, eight kipping pull-ups, six dumbbell thrusters, and ten burpees performed in this order. Measurements of heart rate (HR), oxygen consumption (VO2), rating of perceived exertion (RPE) (1–10 scale), blood lactate (BLA), creatine kinase (CK), excess post-exercise oxygen consumption (EPOC), and muscle oxygen saturation (SmO2) were performed.ResultsTime domains were significantly different for the EMOM and RFT workouts (20 vs. 12 min ± 3 min, p < 0.00). There were significant differences between the EMOM and RFT for HR (153 ± 19 bpm vs. 171 ± 12 bpm, p < 0.01), VO2 (30.8 ± 3 mL/kg/min vs. 38.1 ± 5 mL/kg/min, p < 0.00), RPE (4 ± 1 vs. 7 ± 1, p < 0.00), and EPOC-AUC (3.5 ± 1.2 mL/kg/min vs. 5.0 ± 1.3 mL/kg/min, p < 0.00); however, there were no significant differences in mean SmO2 (p = 0.44). An interaction effect revealed that BLA was lower for the EMOM (6.5 ± 2.7 mmol/L) than the RFT (11.2 ± 2.1 mmol/L) post-exercise (p < 0.00). Conversely, there was no interaction effect for CK (p < 0.16), yet a significant increase was observed from pre- to post-exercise for both the EMOM and the RFT (p < 0.01).ConclusionThe RFT induced greater physiological stress than the EMOM, indicating that prescribed rest intervals significantly affect the metabolic, cardiovascular, and perceptual responses during high-intensity functional exercise. Furthermore, the RFT may provide a greater cardiorespiratory stimulus, while the EMOM may be more suitable for technique development and recovery in trained individuals.